Unleashing Talent: Enhancing Employee Performance through Management, Education, and Experience: Menggali Potensi: Dampak Manajemen Bakat, Tingkat Pendidikan, dan Pengalaman Kerja terhadap Kinerja Karyawan - Dwi Elinda Putri; Vera Firdaus (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study examines the relationship between Talent Management, Education Level, Work Experience, and Employee Performance in a non-profit organization, specifically UPTD SPNF SKB Sidoarjo. The research aims to determine the effect of these factors on employee performance using a sample of 50 employees. Multiple linear regression analysis was employed with the SPSS 22 program for data analysis. The findings demonstrate that talent management positively influences performance, while education level has a negative effect. Additionally, work experience was found to positively impact employee performance. These results suggest the significance of effective talent management strategies, highlighting the role of work experience in enhancing employee performance. This study contributes to the existing body of knowledge in talent management and provides valuable implications for organizations aiming to improve employee performance. Highlights: Talent Management: This study explores the positive impact of effective talent management strategies on employee performance. Education Level: The research reveals a negative relationship between education level and employee performance, emphasizing the need to consider other factors. Work Experience: The study highlights the significant positive influence of work experience on employee performance, underscoring its value in enhancing productivity. Keywords: Talent Management, Education Level, Work Experience, Employee Performance, UPTD SPNF SKB Sidoarjo